Peningkatan Kapasitas Usaha UMKM di Kelurahan Labuh Baru Timur Kota Pekanbaru - Fanny Septya; Rosnita; Roza Yulida; Yulia Andriani (ABDIMAS EKODIKSOSIORA: Jurnal Pengabdian Kepada Masyarakat Ekonomi, Pendidikan, dan Sosial Humaniora (e-ISSN: 2809-3917), 2021)
MSMEs are a fairly hard hit effort during the pandemic. Therefore, increasing the business capacity of MSMEs needs to be done to revive MSME businesses to compete and increase the income of business actors. The purpose of this activity is to increase the business capacity of MSMEs in Labuh Baru Village East of Pekanbaru City. Two activities carried out to achieve the goal are (1) Training in making cassava leaf nori, which is a contemporary food with easily available raw materials, and (2) Socialization of business legality management such as P-IRT needed for MSMEs so that their products can be accepted by the market. This activity is integrated with the activities of students of Riau University, this activity has been able to increase the knowledge and skills of participants about the manufacture of cassava leaf nori and business legality (P-IRT). It is expected that this activity will be able to increase the capacity and income of MSME actors in Labuh Baru Village East of Pekanbaru City.